Foodborne disease outbreaks guidelines for investigation and control (World Health Organization, 2008)
"These guidelines have been written for public health practitioners, food and health inspectors, district and national medical officers, laboratory personnel and others who may undertake or participate in the investigation and control of foodborne disease outbreaks."--P. [4] of cover.